Implementation of the marketing mix and selection of chocholate marketing strategy priorities in a chocolate company in Bali [Implementasi marketing mix serta pemilihan prioritas strategi pemasaran cokelat pada perusahaan cokelat di Bali] - Sukanteri, Ni Putu; Amaral, Putu Anglila; Lestari, Putu Fajar Kartika; Tamba, I Made (Jurnal Teknologi & Industri Hasil Pertanian, 2024)
Chocolate is a processed product derived from cocoa beans that has undergone fermentation, drying, roasting, and grinding to produce high-quality cocoa powder. The processing of chocolate in a company involves many lengthy stages. Implementing a marketing mix is used as a technique to increase sales. The company needs to identify the superior products favored by consumers to develop priority marketing strategies. This study aims to analyze the application of the marketing mix in the chocolate industry and generate prioritized marketing strategies for the superior chocolate products produced by a company in Bali. The research method used is the Analytical Hierarchy Process (AHP). The results indicate that the marketing mix includes chocolate products such as chocolate cream, chocolate bars, and liquid chocolate. Product pricing depends on the form, with the most apparent pricing being for chocolate bars, calculated based on weight in grams. The production site is located at the main factory, which processes cocoa into chocolate cream, chocolate bars, and liquid chocolate, allowing consumers to experience the chocolate processing firsthand and try packaging chocolate at the factory. Chocolate promotion is continuously carried out through offline and online media, such as the company's website, which provides background information on chocolate production to the industry in Bali. The priority in chocolate marketing, based on the Analytical Hierarchy Process, is chocolate cream, followed by chocolate bars and liquid chocolate.